Genetic diversity and population structure of Meretrix petechialis in China revealed by sequence-related amplified polymorphism markers - Xu, Qiaoyue; Zheng, Junhong; Nie, Hongtao; Wang, Qingzhi; Yan, Xiwu (PeerJ, 2020)
Genetic variation in nine stocks of Meretrix petechialis collected from China was analyzed using sequence-related amplified polymorphism (SRAP) markers. Eight primer pairs produced 132 polymorphic loci with an average of 16.5 loci per primer pair. A population from Jiangsu had the highest percentage of polymorphic loci at 27.27%, suggesting that these resources had a rich genetic diversity. The Nei’s gene diversity of the nine populations ranged from 0.0647 to 0.0793; a population from Shandong was the lowest and a population from North Korea the highest. The Shannon’s information index was between 0.1023 and 0.1202, with the lowest in the Shandong population and the highest in the Jiangsu population. The Nei’s unbiased genetic distance between the nine populations was 0.0243–0.0570 and the genetic similarity was 0.9446–0.9760; the genetic distance between Guangxi and Shandong populations was the furthest (0.0570) and the genetic distance between Shandong and Jiangsu populations was the closest (0.0243). Nei’s gene diversity analysis indicated that the genetic variance was mainly found within individual geographical populations, and the analysis of molecular variance revealed low but significant genetic differentiation among local and regional populations. The limited gene flow (Nm = 0.555) was inferred as a major reason for the extent of genetic differentiation in M. petechialis. The results obtained here indicated that M. petechialis have high degree of genetic diversity and the potential of further breeding with excellent germplasm resources. This study provides a scientific basis for the protection of germplasm resources and the breeding of M. petechialis.
Keywords: Meretrix petechial; Genetic diversity; Polymorphism; SRAP; Genetic structure